التقديس في الفكر المسيحي وآثاره في تشكيل العقائد والطقوس الليترجية - يخلف، سهام; رحمانى، سعيد (جامعة الأمير عبد القادر للعلوم الإسلامية - كلية أصول الدين, 2022)
يتناول هذا البحث تقديم دراسة تحليلية نقدية لظاهرة التقديس في المسيحية، من خلال البحث عن معانيها اللاهوتية في الفكر المسيحي وتتبع تاريخ نشأتها، ثم البحث عن أهم الأسباب التي ساعدت في ظهورها والتي توزعت ما بين أسباب فكرية وسياسية، ثم استنتاج أهم آثار هذه الظاهرة على الفكر الديني المسيحي وعلى المظاهر الطقسية في الكنيسة المسيحية. This research consists of presenting a critical analytical study of the phenomenon of sanctification in Christianity, researching its theological meanings in Christian thought and tracing the history of its creation, then looking for the most important causes that contributed to its emergence and that were divided. Between intellectual and political reasons, then deduce the most important effects of this phenomenon on the thought of Christian religious and on liturgical manifestations in the Christian church.
Keywords: الكنيسة المسيحية -- المظاهر الطقسية -- الأفكار اللاهوتية